The Declaration of Independence - Hurt, Avery Elizabeth (America's most important documents., 2019)
Presents a brief history of the origins and writing of the Declaration of Independence and discusses the importance of this document to American history. Includes photographs, illustrations, a glossary, an index, and resources for further reading.